Risk Factors for Sexual Dysfunction Among Women and Men: A Consensus Statement From the Fourth International Consultation on Sexual Medicine 2015. Issue 2 (1st February 2016) - McCabe, Marita P.; Sharlip, Ira D.; Lewis, Ron; Atalla, Elham; Balon, Richard; Fisher, Alessandra D.; Laumann, Edward; Lee, Sun Won; Segraves, Robert T.
ABSTRACT: Introduction: This article presents a review of previous research concerning risk factors for sexual dysfunction in women and men. Aim: The aim is to evaluate past research studies to determine the contribution of all risk factors to the development and maintenance of sexual dysfunction among women and men. Methods: Studies were organized under a biopsychosocial framework, with the bulk of studies of women and men having investigated the role of biological factors. Main Outcome Measures: The outcome measures were the data on factors for sexual dysfunction. Results: Many more studies investigated risk factors for sexual dysfunction in men than in women. For women and men, diabetes, heart disease, urinary tract disorders, and chronic illness were significant risk factors for sexual dysfunction. Depression and anxiety and the medications used to treat these disorders also were risk factors for sexual dysfunction in women and men. In addition, substance abuse was associated with sexual dysfunction. Many other social and cultural factors were related to sexual dysfunction in women and men. Conclusion: Psychosocial factors are clearly risk factors for sexual dysfunction. Women and men with sexual dysfunction should be offered psychosocial evaluation and treatment, if available, in addition to medical evaluation and treatment. The impact of social and cultural factors on sexual function requires substantially more research. The evidence that erectile dysfunction is a harbinger of other forms of cardiovascular disease is strong enough to recommend that clinical evaluation for occult cardiovascular disease should be undertaken in men who do not have known cardiovascular disease but who develop organic erectile dysfunction, especially in men younger than 70 years.